The Penn Vet Working Dog Center Fit to Work Program: A Formalized Method for Assessing and Developing Foundational Canine Physical Fitness - Farr, Brian D.; Ramos, Meghan T.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2020)
Fit to Work is a formalized working dog foundational physical fitness assessment and development program. The Penn Vet Working Dog Center developed this program to address the needs of working dog handlers, trainers, and programs for simple, effective, and efficient methods to develop and assess working dog physical fitness. Fit to Work focuses on the foundational fitness modalities of strength, stability, mobility, and proprioception. The Penn Vet Working Dog Center piloted and refined this program over three months in a closed population of 31 working dogs in training. Fit to Work consists of posture development and maintenance, warm-up and cool-down routines, training exercises, and assessment methods. To simplify implementation for dogs and personnel, the foundational training program incorporates a discrete number of exercises, standardized progression steps, defined criteria for progression, and a reduced emphasis on learned behaviors. Fit to Work also enables safe and progressive assessment of foundational fitness through a tiered and inexpensive process. Future work will focus on validation of training and assessment methods, development of assessment standards, and correlation of physical fitness with operational performance.